A systematic decision model for selecting urban zero-emission vehicle technologies - Yildirim, Betul; Kara, Betul; Ayyildiz, Ertugrul; Aydin, Nezir (ELSEVIER, 2026)
Urban transportation systems urgently require decarbonization to address climate change and achieve the Sustainable Development Goals. This study presents a novel decision-making framework that integrates Picture Fuzzy Stepwise Weight Assessment Ratio Analysis (PiF-SWARA) and Picture Fuzzy Integrated Simple Weighted Sum Product (PiF-WISP) to systematically evaluate zero-emission vehicle (ZEV) technologies for urban use. Focusing on T & uuml;rkiye, the research defines and weights fourteen criteria, including environmental, economic, and social impacts, through expert consultation. Six main ZEV alternatives, including battery electric buses, fuel cell electric buses, battery electric cars, compressed natural gas buses, and light rail vehicles, are assessed using this hybrid approach, which accounts for uncertainty in expert judgment. The results show that carbon emission reduction, safety systems, and charging/refueling infrastructure are the most influential criteria in determining optimal ZEV options, with weights of 0.0080, 0.0852, and 0.0842, respectively. Plug-in hybrid electric buses emerge as the top-ranked alternative. This study offers a practical tool to guide policymakers and urban planners toward sustainable, low-carbon transport solutions.
Keywords: Zero-emission vehicles; Sustainability; Urban deployment; Multi-criteria decision making; Picture fuzzy sets; Construction & Building Technology; Science & Technology - Other Topics; Energy & Fuels